Tahlil al-Ma'na 'An al-Ayat al-Tsalatsah Min Surah al-Nas - Saputra, Syukri Hamdi (Arabiyatuna : Jurnal Bahasa Arab, 2018)
This article seeks to analyze the meaning of the application of the semantic theory of the first three verses of Surat al-Nas. The purpose of this thesis is to analyze the meanings of words in terms of context. The choice of these words, and to identify the linguistic function in the use of words and composition in these verses in the communication of meaning and usefulness, and stand on the moral characteristic of the three words in the theory of semantic fields. Of the choice of these three words (Lord, King, God) to indicate God is to arrange the reasons that show that God Almighty to the people and worshiped him. And each linguistic element fits and helps the expression of this meaning, and the use of words in these verses with this structure helps to indicate the meaning of order of reason and the greatness of the components of the sura. The whole word is put into a special meaning and installed in a special structure to look at its own characteristic.